LITERATURE REVIEW PENGEMBANGAN MEDIA EDUKASI KESEHATAN MASYARAKAT : TREN, INOVASI, DAN EFEKTIVITAS - Eka Cahyani; Najwa Safira Hasibuan; Nur Anisa; Anisa Marsya Agustin; Miftahurrahmah El Hayatli (CV. Adiba Aisha Amira, 2025)
The development of information and communication technology has driven innovation in health education media, ranging from traditional print media to digital and interactive social media platforms. These various media formats have the potential to reach broader audiences and enhance the effectiveness of health message delivery. However, the effectiveness of educational media largely depends on selecting the appropriate type of media based on the characteristics of the target audience and the method of information delivery. Therefore, a comprehensive literature review is necessary to understand the trends in health education media innovation and the evidence of its effectiveness in improving public knowledge and behavior. The purpose of this literature review is to examine the development of public health education media, focusing on innovation trends and their effectiveness. This study employs a literature review method by analyzing relevant articles sourced from Google Scholar. The findings indicate that innovations in educational media—such as the use of interactive videos, social media, and mobile applications—have a positive impact on increasing public knowledge and health-related behaviors. Furthermore, the effectiveness of educational media is significantly influenced by content relevance, delivery methods, and audience engagement. These findings offer a comprehensive overview that can serve as a foundation for developing more adaptive and effective health education media to support health promotion in communities.